PENGARUH KUALITAS PELAYANAN, TARIF DAN FASILIAS TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA RUMAH SAKIT UMUM DAERAH EMBUNG FATIMAH KOTA BATAM - Anggraeni, Dewi; Kurniawan, Putu Hari (SCIENTIA JOURNAL, 2019)
Developments in the service sector are rapidly increasing, one of which. health services such as hospitals, health centers, clinics, medical centers and others. Hospital is one of the institutions engaged in health services with the responsibility of providing treatment and providing care. The purpose of this study is to determine the effect of service quality, rates and facilities on patient satisfaction. Where the independent variable is service quality, rates and facilities, affects patient satisfaction as the dependent variable. The population used in this study were patients at Embung Fatimah Hospital, with a sample of 100 respondents. The sample in this study used simple random sampling and data collection using questionnaires. Quantitative analysis includes validity, reliability, classic assumption test, multiple linear analysis, coefficient of determination (R2), f test and t test. Data from this study were processed using SPSS version 20. The results of this study were that service quality partially had a positive and significant effect on patient satisfaction, rates had a positive and significant effect on patient satisfaction and facilities had a positive and significant effect on patient satisfaction. While simultaneous results, service quality, tariffs and facilities have a significant influence on patient satisfaction.